A decision-making framework for evaluating enterprise resource planning systems in a high-tech industry. Issue 3 (3rd May 2020) - Lee, Amy H. I.; Chen, Shun-Chien; Kang, He-Yau
ABSTRACT: In recent years, the adoption of enterprise resource planning (ERP) is becoming essential for achieving fast and transparent information exchange, avoiding unnecessary waste and maintaining coordination within a firm and among partners in a supply chain. However, the implementation of an ERP system often fails, and one major reason is that the selected ERP system is not suitable for the firm. Therefore, a good evaluation framework for selecting the most appropriate ERP system is necessary. This study proposes a framework, which integrates decision-making trial and evaluation laboratory (DEMATEL), analytic network process (ANP), VlseKriterijumska Optimizacija I Kompromisno Resenje in Serbian (VIKOR) and fuzzy set theory, for the evaluation of ERP systems. First, the fuzzy DEMATEL is used to understand the direct and indirect relationships among the criteria. Second, the fuzzy ANP is adopted to calculate the importance weights of the sub-criteria. Finally, the most appropriate ERP system is obtained by the fuzzy VIKOR. The proposed decision-making framework is applied to a firm in the high-tech industry in selecting the most appropriate ERP system. The results show that the proposed framework can help firms evaluate ERP systems effectively by collecting experts' opinions in an uncertain environment.